Comparative analysis of Advanced and Immediate Life Support acquisition degree. - Antonio Cárdenas Cruz; Eva Peregrina Caño; Dolores Cárdenas Cruz; Isabel Santiago Suárez; Miguel Ángel Martín Piedra; Francisco Manuel Parrilla Ruiz (Universidad de Murcia, 2021)
Cardiac arrest (CA) is a major public health problem in developed countries. According to the Spanish Cardiopulmonary Resuscitation Council, in Spain there are around thirty thousand deaths a year and about twenty thousand resuscitation attempts, and yet until very recently medical students did not receive formal training in Advanced Life Support (ALS). With the introduction in 2018 of a new subject, we faced the problem of not having established what type of Life Support was appropriate for our students. As a result, the aim of this study is to analyze in a comparative way the degree of acquisition of competences in ALS and Immediate Life Support (ILS) and their temporal evolution by the students of fifth and sixth year (Medicine Degree) of the University of Granada (UGR). To achieve that aim, we obtained the data in an initial evaluation to the medical students who enrolled in the optional subject of Advanced Life Support in the Faculty of Medicine (UGR), during the months of October and November (2019). This evaluation was carried out by external evaluators and was based on the ERC 2015 guidelines. Months later, a reassessment that was carried out during the months of February and March 2020 to the same sample of students gave us the data for the comparison. Data showed that the degree of acquisition of competencies related to the ILS exceeds the level of acquisition of the competences included within the ALS, and that the effect of the Oblivion Curve for the competences included in the ILS is lower than those included in the ALS. We could conclude that the competences that are integrated within the ILS present a higher level of acquisition and a lesser effect on the forgetting curve, so they should become part of the curricular content of the UGR Medical Degree.